2020
DOI: 10.1136/bjophthalmol-2020-317576
|View full text |Cite
|
Sign up to set email alerts
|

Retinal findings in hospitalised patients with severe COVID-19

Abstract: AimTo identify retinal findings using dilated eye examination, which are possibly related to SARS-CoV-2 infection in hospitalised patients with confirmed severe COVID-19.MethodsIn this cross-sectional study, hospitalised patients with confirmed severe COVID-19 in a single referral centre for the treatment of COVID-19, in Santo André, São Paulo Metropolitan Area, Brazil, underwent dilated eye examination of both eyes performed by a retina specialist. Findings were recorded using a portable digital fundus camera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
133
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(147 citation statements)
references
References 14 publications
(17 reference statements)
5
133
0
9
Order By: Relevance
“…All these could be considered signs of retinal vascular impairment following thrombotic complications. 7 , 8 , 9 , 30 , 31 Hitherto, only one report conducted by Savastano et al used OCTA imaging in Covid-19 patients. 32 The authors demonstrated a reduction of perfusion density of the radial peripapillary capillary plexus in Covid-19 patients compared to healthy controls after one month from infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these could be considered signs of retinal vascular impairment following thrombotic complications. 7 , 8 , 9 , 30 , 31 Hitherto, only one report conducted by Savastano et al used OCTA imaging in Covid-19 patients. 32 The authors demonstrated a reduction of perfusion density of the radial peripapillary capillary plexus in Covid-19 patients compared to healthy controls after one month from infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was not possible to clearly establish whether these signs were secondary to COVID-19 or just incidental findings, given the high presence of comorbidities in the general population. 7 , 8 , 9 Optical coherence tomography angiography (OCTA), a new non-invasive imaging technique, may provide qualitative and quantitative features of retinal and choroidal vascularization and could monitor the changes of vascular perfusion in patients with Covid-19. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“… 19 Further, in a case series of patients with severe COVID-19, 10 out of 18 patients had retinal abnormalities such as flame-shaped haemorrhages or cotton-wool spots, suggesting involvement of retinal vasculature. 20 Although our patient was not critically ill, it cannot be ruled out that the haemorrhage was related to the SARS-CoV-2 infection. Contact tracing after the positive PCR-test was obtained did not reveal any transmission to hospital staff.…”
Section: Discussionmentioning
confidence: 77%
“…They suggested a potential role of fundus examination in patients with co-infection. In contrast, Pereira et al have reported the findings of a cohort of 18 hospitalized patients from Brazil, of whom 10 (55.5%) had detectable retinal lesions (hemorrhages, cotton wool spots) on dilated fundus examination via photography [ 18 ].…”
Section: Discussionmentioning
confidence: 99%